2022
DOI: 10.3390/ijms232315401
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199a-3p Induces Mesenchymal to Epithelial Transition of Keratinocytes by Targeting RAP2B

Abstract: Cutaneous squamous cell carcinoma (CSCC) is an epidermal skin cancer that evolves from normal epidermis along several pre-malignant stages. Previously we found specific miRNAs alterations in each step along these stages. miR-199a-3p expression decreases at the transition to later stages. A crucial step for epithelial carcinoma cells to acquire invasive capacity is the disruption of cell–cell contacts and the gain of mesenchymal motile phenotype, a process known as epithelial-to-mesenchymal transition (EMT). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…For instance, the level of miR-199b-3p was elevated in colon cancer, and its inhibition increased the anti-tumor effects of chemotherapeutic cetuximab [ 36 ]. Another study indicated that miR-199a-3p inhibited cell growth and the epithelial-to-mesenchymal transition (EMT) process in Cutaneous squamous cell carcinoma through targeting Ras-associated protein B2 (RAP2B) [ 37 ]. According to our results, the transfection of miR-199a-5p mimic reduced the proliferation, invasion and stemness of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the level of miR-199b-3p was elevated in colon cancer, and its inhibition increased the anti-tumor effects of chemotherapeutic cetuximab [ 36 ]. Another study indicated that miR-199a-3p inhibited cell growth and the epithelial-to-mesenchymal transition (EMT) process in Cutaneous squamous cell carcinoma through targeting Ras-associated protein B2 (RAP2B) [ 37 ]. According to our results, the transfection of miR-199a-5p mimic reduced the proliferation, invasion and stemness of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%